Transendensi Feminin Tokoh Mata Hari dalam Novel Namaku Mata Hari Karya Remy Sylado: Penelitian - Nurgian Utina, Siti; Hinta, Ellyana; Achmad Bagtayan, Zilfa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines Remy Sylado's novel Namaku Mata Hari, which portrays Mata Hari's struggles as a woman facing a marriage that does not meet her expectations. Initially, Mata Hari perceives marriage as a path to happiness and self-actualization. However, she instead experiences domestic violence and infidelity, which deprive her of freedom and her rights as a woman. These conditions drive her to resist patriarchal norms through a transformative process toward becoming an independent woman. This research focused on two main aspects: the concept of feminine transcendence and the representation of women, as exemplified by Namaku Mata Hari. The analysis employed Simone de Beauvoir's existentialist feminist theory as presented in The Second Sex, which explored women's transcendence of oppression through freedom and consciousness in defining their identities. The study employed a descriptive qualitative method, utilizing reading, observation, and note-taking techniques. The findings revealed that Mata Hari succeeded in liberating herself from oppression by assuming the role of an entertainer who introduced Indonesian culture to the world, thereby achieving both economic and intellectual independence.